Evaluation of the immunoprotective potential of recombinant EtMIF as a subunit vaccine candidate against Eimeria tenella infection in chickens - Bai, Rui; Wang, Hui; Guo, Jiale; Pei, Yang; Li, Yongbin; Zhu, Shuying; Lv, Chenyang; Li, Jianhui; Cui, Xiaozhen; Lv, Xiaoling (Frontiers in Immunology, 2025)
IntroductionEimeria tenella is recognized as the most pathogenic species of chicken coccidia. Infection with E. tenella results in digestive disorders and hemorrhagic diarrhea in chickens. Furthermore, E. tenella has recently shown high incidence and mortality rates. Therefore, developing effective vaccines is vital for controlling this disease. Macrophage migration inhibitory factor (MIF) is recognized as a key upstream cytokine that mediates innate and adaptive immune responses, drawing significant attention.MethodsIn this study, we amplified the E. tenella MIF (EtMIF) gene sequence, constructed the pET-28a-EtMIF prokaryotic expression vector, and expressed and purified the recombinant EtMIF (rEtMIF) protein. The rEtMIF protein localization was determined using immunofluorescence staining, and its immunoprotective efficacy at three different doses (50 µg, 100 µg, and 150 µg) was subsequently evaluated through animal trials.ResultsThe rEtMIF protein was approximately 12 kDa in size and primarily existed in a soluble form. The optimal induction conditions were 37°C for 4 hours, and the optimal imidazole elution concentration was 500 mmol/L. The rEtMIF protein was recognized by 6×His-tagged monoclonal antibodies, infection-positive chicken serum, and rabbit anti-rEtMIF polyclonal antibodies. Indirect immunofluorescence analysis demonstrated that the rEtMIF protein was localized both on the surface and within the merozoites of E. tenella. Evaluation of immune protection showed that weight gain in the immunized groups was significantly higher than in the non-immunized group (P < 0.05). Additionally, intestinal lesion scores and oocyst output were significantly reduced (P < 0.05). Among all groups, the 50 µg rEtMIF group achieved the highest anticoccidial index (ACI) value of 161.48. Levels of serum antibodies and cytokines, including IL-1, IL-8, IFN-γ, and TNF-α, were significantly elevated in the immunized groups, indicating that recombinant rEtMIF can stimulate both humoral and cellular immune responses in chickens.DiscussionThis study support the potential of recombinant rEtMIF as a promising candidate for developing vaccines against chicken coccidiosis.